Prediction of bed pressure drop, fluctuation and expansion ratios for three-phase fluidization of ternary mixtures of dolomite in a conical conduit. Issue 1 (31st December 2016) - Padhi, R.K.; Dora, D.T.K.; Mohanty, Y.K.; Roy, G.K.; Sarangi, B.
Abstract: Hydrodynamics of conical fluidized bed differ from that of columnar beds by the fact that a velocity gradient exists along the axial direction of the bed. The gas–liquid–solid fluidized bed has emerged in recent years as one of the most promising devices for three-phase operations. Such a device is of considerable industrial importance as evident from its wide applications in chemical, refining, petrochemical, biochemical processing, pharmaceutical, and food industries. To explore this, experiments have been carried out to find the bed pressure drop, bed fluctuation, and expansion ratios for ternary mixtures of dolomite in a three-phase conical fluidized bed. The effect of superficial liquid and gas velocity, initial static bed height, average particle size, and cone angle on the above-mentioned three responses have been studied. Mathematical models have been developed for the responses using both dimensional and statistical analyses. The calculated values of the responses from the developed models have shown a very good agreement with the experimental ones.